Integrating performance management and enterprise risk management systems : emerging issues and future trends - Spanó, Rosanna; Zagaria, Claudia (Emerald points., 2022)
Integrating Performance Management and Enterprise Risk Management Systems offers a novel understanding of the multifaceted shades that surround the long called-for and yet not realised integration between performance management and enterprise risk management systems. Spanò and Zagaria depart from the idea that the main limitations so far refer to the jeopardization of extant contributions, the lack of a fully holistic perspective of analysis and interpretation, and the need to closely consider potential opportunities and threats in the current VUCA (volatile, uncertain, complex, and ambiguous) world - issues concerning ethical concerns and accountability pressures, power dynamics, social and sustainability implications, and technological impacts. Their study supports a substantive integration of performance management and enterprise risk management systems encompassing the current theoretical debates and the multiple practical and policy interventions, highlighting overlaps and gaps, and fostering a more systematic approach towards the embeddedness of unified routines and behaviours. The authors suggest looking at performance management and enterprise risk management systems as logics rather than functions, as languages rather than tools, and devoting major attention to soft variables in addition to hard ones, towards a novel comprehension of timely dynamics paramount for academics, practitioners and policy makers.